Korelasi Tingkat Pendidikan Dan Sikap Ibu Hamil Dalam Kunjungan Antenatal Care Di Puskesmas Tobadak Kabupaten Mamuju Tengah - Manuntungi, Andi Ernawati; Sallo, Andi Kamal M.; Susanti, Susanti; Musdalifah, Musdalifah (Barongko: Jurnal Ilmu Kesehatan, 2022)
Antenatal care services are services provided by health workers to pregnant women to maintain their pregnancy until delivery and obtain a healthy baby and to detect as early as possible pregnancy abnormalities in pregnant women and detect abnormalities in the fetus. The high maternal mortality rate is caused by pregnant women ignoring the importance of danger. -danger in pregnancy. The aim of this study was to determine whether there was a relationship between the level of education and attitudes of pregnant women and Antenatal Care visits at the Tobadak Community Health Center. The type of research used is Observational Analytical, with a Cross Sectional approach, a population of 68 using the Slovin formula, with Purposive Sampling. The results of univariate analysis showed that of the 41 samples, the majority of pregnant women had high education (≥high school), the majority had low education (≤ graduated from junior high school), while 39 mothers had a supportive attitude, and 2 pregnant women who did not support it. The results of the bivariate analysis show the level of education (????????????????????????=0.662), and the attitude of pregnant women (????????????????????????=0.475). The conclusion is that education and attitudes of pregnant women are not related to Antenatal Care visits. It is recommended for health workers to increase health promotion and health education, especially Antenatal Care visits to pregnant women.